CORRELATION ANALYSIS OF THE INTERDEPENDENCE OF ECONOMY'S INNOVATION AND CREATIVITY INDICES - Anna Kniazevych; Ruslan Strilchuk; Serhii Kraychuk (Baltic Journal of Economic Studies, 2024)
Creativity and the generation of innovative solutions are means of solving the problems of slow economic development and resistance to instability that have been observed in recent years. The key role of creativity of individuals and groups of workers as a defining feature of modern economic life is increasingly recognised. There is a consensus that people, as a source of creativity, are now a critical resource of the new era. In the new model of economic development, creativity, knowledge and free access to information are seen as powerful drivers of development and catalysts of globalisation. The subject of the research is to study the relationship between innovation and creativity in the economic sphere. In particular, the article examines how the creativity of various economic subjects affects the level of innovative indicators, which synthetically reflect the possibilities of achieving the goals of innovative development. The research methodology includes the use of global reports on innovation and creativity indices, as well as scientific sources on this topic. The study uses the methods of critical analysis of scientific papers and international rankings, comparison and correlation of interdependent indicators. The purpose of the research is to assess the relationship between creativity and the level of innovative indicators, which synthetically show the possibilities of achieving the goals of innovative development. Creativity of business entities and mechanisms for generating innovative solutions are determining factors of success of modern post-industrial societies. In most developed countries, long-term economic growth is supported by innovation and creativity of various economic entities. To create the research algorithm, the authors defined the chain of concepts "sustainable development – innovation – creativity". To assess and analyse creativity, the study uses methodological tools that can be applied in global and local contexts. The most well-known indices are the Global Innovation Index (GII), the Global Creativity Index (GCI), the City Creativity Index (CCI), and the Hong Kong Creativity Index (HKCI). The general correlation coefficients between the global innovation index and the creativity indices of some countries have been calculated. According to the results of the calculations, the correlation coefficients of creativity and innovation are very positive. They are closely related and belong to the group of significantly correlated indicators. This means that there is a very high correlation between innovation and creativity in the economies studied. Conclusions. The positive correlation between innovation and creativity indices confirms, in general and in specific terms, a close relationship between innovation and creativity in the economies of different countries. This may indicate that countries or regions with a higher level of economic development have higher rates of creativity and vice versa. The research demonstrates the importance of innovation for the development of creativity in the economy. Understanding this interaction can serve as a basis for designing strategies and policies aimed at promoting innovative development and the growth of creative potential. The economies of Poland, Bulgaria and Ukraine, which were studied in detail, are not innovative enough. The countries studied represent different levels of economic development and are in the phase of post-industrial development, which requires effective innovation policies and measures to support creativity. In order to increase the level of innovation and creativity, it is necessary to involve national governments and organisations (especially the European Union) that can contribute to this. The conclusions point to the need to develop comprehensive approaches to support innovation and creativity in the economies of the countries studied. This may include not only effective strategies to stimulate research and development, but also policies aimed at the cultural environment, education and other areas.